PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN SEBAGAI VARIABEL KONTROL - Helga Adeline Halim; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to obtain empirical evidence on the influence of applying corporate governance to firm value in Indonesia. Corporate governance was measured by using CGPI score, while firm value was measured by using Tobin’s Q. This study also used firm size, firm age and financial crisis as control variables. This study was conducted on companies listed in Bursa Efek Indonesia that obtained CGPI ranking from 2001-2015 with a sample of 194 observations. The result of this study showed that corporate governance had positive and significant affect on firm value, while firm size, firm age and financial crisis had negative and significant affect on firm value.